2017
DOI: 10.3847/1538-4357/aa886a
|View full text |Cite
|
Sign up to set email alerts
|

Variable Dynamics in the Inner Disk of HD 135344B Revealed with Multi-epoch Scattered Light Imaging

Abstract: We present multi-epoch Very Large Telescope/Spectro-Polarimetric High-contrast Exoplanet REsearch observations of the protoplanetary disk around HD 135344B (SAO 206462). The J-band scattered light imagery reveal, with high spatial resolution (∼41 mas, 6.4 au), the disk surface beyond ∼20 au. Temporal variations are identified in the azimuthal brightness distributions of all epochs, presumably related to the asymmetrically shading dust distribution in the inner disk. These shadows manifest themselves as narrow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 73 publications
2
55
0
1
Order By: Relevance
“…Hashimoto et al 2011;Mayama et al 2012;Avenhaus et al 2014a,b;Garufi et al 2014;Thalmann et al 2015;Akiyama et al 2016;Monnier et al 2017;Bertrang et al 2018), with the new SPHERE / IRDIS instrument being particularly successful at imaging disks at high signal-to-noise ratio (e.g. Pohl et al 2017;Stolker et al 2017). An overview of recent SPHERE results can be found in Garufi et al (2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al 2011;Mayama et al 2012;Avenhaus et al 2014a,b;Garufi et al 2014;Thalmann et al 2015;Akiyama et al 2016;Monnier et al 2017;Bertrang et al 2018), with the new SPHERE / IRDIS instrument being particularly successful at imaging disks at high signal-to-noise ratio (e.g. Pohl et al 2017;Stolker et al 2017). An overview of recent SPHERE results can be found in Garufi et al (2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced Band 3 and Band 4 data (FITS files) are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/ qcat?J/A+A/619/A161 Benisty et al 2015Benisty et al , 2017Pérez et al 2016;Stolker et al 2016Stolker et al , 2017Follette et al 2017;Dong et al 2018) are being observed at mm-wavelength continuum emission with ALMA and in scattered light in the near-infrared (NIR) with VLT/SPHERE (Beuzit et al 2008) and Gemini/GPI (Macintosh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Left panel: ALMA Band 4 observations of HD 135344B at 1.9 mm. Right panel: same image with the contours of the spiral arms observed with SPHERE (Stolker et al 2017) overlaid in white. The panel in the upper left corner shows a zoom into the inner regions, with a colourmap enhancing the emission from the central point-source.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to new capabilities of high resolution instruments such as ALMA, VLT/SPHERE and Gemini/GPI, many features have been identified in protoplanetary disks and in particular in transition disks (TDs). A number of studies reveal rings (e.g., Isella et al 2016;Pohl et al 2017b;Muro-Arena et al 2018), lopsided emission (e.g., Casassus et al 2013;Cazzoletti et al 2018), spirals (e.g., Pérez et al 2016;Dong et al 2018;Muto et al 2012;Stolker et al 2017;Benisty et al 2017;Uyama et al 2018), and shadows (e.g., Marino et al 2015;Stolker et al 2017;Casassus et al 2018;Benisty et al 2018). Among other mechanisms, planets Based on observations performed with SPHERE/VLT under program ID 099.C-0891(A) and 099.C-0147(A).…”
Section: Introductionmentioning
confidence: 99%